2005
DOI: 10.1089/jir.2005.25.485
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of IFN-β1a Treatment Alone or Associated with Pentoxifylline in Patients with Relapsing-Remitting Multiple Sclerosis (RRMS)

Abstract: Interferon-beta1a (IFN-beta1a) and pentoxifylline (PTX) are reported to be active in relapsing-remitting multiple sclerosis (RRMS), but the mechanisms are not completely understood. In two groups of RRMS patients, we studied the phenotype of peripheral lymphocytes and the level of several cytokines both in sera and in supernatants of activated peripheral blood mononuclear cells (PBMC) before and after 8 months of therapy with IFN-beta1a alone or associated with PTX. Our data indicate that patients with RRMS, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…Results of our study were supported by the results of the study conducted by Pede et al in 2005, in which no clear difference in the overall T cells levels was found between the two treatment groups (which were similar to ours) [17]. In a study by van Oosten et al [4], no convincing and consistent effects of pentoxifylline were shown on the inflammatory cells and the EDSS of MS patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results of our study were supported by the results of the study conducted by Pede et al in 2005, in which no clear difference in the overall T cells levels was found between the two treatment groups (which were similar to ours) [17]. In a study by van Oosten et al [4], no convincing and consistent effects of pentoxifylline were shown on the inflammatory cells and the EDSS of MS patients.…”
Section: Discussionsupporting
confidence: 90%
“…Treatment with IFN-β in multiple sclerosis inhibits the production and migration of the T lymphocytes and also changes the cytokine profile to generate anti-inflammatory cytokines. Pentoxifylline have shown in numerous studies that they inhibit inflammatory factors such as TNF and interleukins and also accelerates the conversion of the immune response from Th1 to Th2 (IL-4, IL-10) cells [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…This suppression of pro-inflammatory T cells upon IFN-b therapy might be achieved by rescue of the impaired susceptibility to apoptotic elimination of autoreactive T cells 65 or by recovery of CD4 + CD25 + regulatory T-cell effector functions. 66,67 Whatever the precise molecular mechanism, our data may point towards a somewhat selective immunomodulation because IFN-btreated patients had reduced proliferative reactivity to MOG but unaltered responses to TT, possibly by suppressing the expansion of pro-inflammatory T cells in an ongoing autoimmune response while leaving the underlying pool of unrelated memory T cells unaffected. The outcome of an antigen-specific reduction of cell proliferation under immunotherapy is likely to be potentiated by the generally impaired capability of T cells to produce considerable levels of IFN-c, be it in response to MOG or to TT, thus supporting earlier observations on the potential of peripheral lymphocytes to mount cytokine responses.…”
Section: Discussionmentioning
confidence: 91%
“…We previously showed that in human Treg DA subserves an autocrine/paracrine inhibitory circuit operated by DR D5 receptors, ultimately resulting in reduced suppressive efficiency of Treg [29], thus DR D5 dowregulation resulting in the desensitization of Treg to the inhibitory effects of DA during therapy with IFN-β could represent a novel mechanism involved in the restorative effect of IFN-β treatment on Treg function in MS patients [17,18,19,20,21]. …”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that IFN-β treatment may restore Treg frequency and function in MS patients [17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%